ANALISIS KINERJA KEUANGAN PADA PT ASTRA INTERNATIONAL TBK PERIODE 2024-2025 - christina shanti sardjito; Mardisuroso; Made Okta Saputra; Prof. Dr. Sri Hermuningsih, MM (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract This research is driven by fluctuations in macroeconomic conditions that have a significant impact on the stability of the automotive and conglomerate sectors in Indonesia. The study aims to conduct a comprehensive evaluation of the financial performance of PT Astra International Tbk (ASII) during the 2024-2025 period, focusing on the company’s operational efficiency and financial resilience. Utilizing a descriptive quantitative method, this research analyzes secondary data from consolidated financial statements through the calculation of various fundamental indicators, such as liquidity, activity, solvency, and profitability ratios. The results of the analysis indicate that strategic liquidity parameters are in an excellent category, with a Quick Ratio at an ideal level of 100%, despite pressure on net profit margins as reflected in the decline in earnings quality compared to the previous period. The study concludes that while the entity's capital structure remains solid and controlled, optimization of asset management and operational cost efficiency audits are required to restore profitability. The implications of this research suggest that management should implement a cost leadership strategy to maintain creditor confidence and mitigate financial risks amidst ongoing market volatility.